2007
DOI: 10.1093/jn/137.3.756s
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Basis of Microflora-Host Interactions1,

Abstract: Mucosal surfaces represent the main sites in which environmental microorganisms and antigens interact with the host. In particular the intestinal mucosal surfaces are in continuous contact with a heterogeneous population of microorganisms of the endogenous flora and are exposed to food and microbes. As a result, the immune system of the host has to discriminate between pathogenic and commensal microorganisms. This article reviews the types of sentinel cells that continuously sense the environment and coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
84
0
21

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 185 publications
1
84
0
21
Order By: Relevance
“…The results suggest that T-cell reactivity was reduced by FLD feeding. This finding is similar to the results obtained after oral administration of probiotics in human subjects or rodents (Pessi et al, 1999;Winkler et al, 2007). Furthermore, we found that the production of inflammation cytokines such as TNF-a and IL-8, also significantly decreases in the blood cells of FLD-fed piglets.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results suggest that T-cell reactivity was reduced by FLD feeding. This finding is similar to the results obtained after oral administration of probiotics in human subjects or rodents (Pessi et al, 1999;Winkler et al, 2007). Furthermore, we found that the production of inflammation cytokines such as TNF-a and IL-8, also significantly decreases in the blood cells of FLD-fed piglets.…”
Section: Discussionsupporting
confidence: 92%
“…Various types of strain-specific immunomodulations can be brought about, as observed in numerous trials (Winkler et al, 2007). With regard to FLD, it has been reported that colostrum from FLD-fed sows showed greater mitogenic activity compared with that from dry feed-fed sows, and improved the health status of their piglets via the colostrum (Demeckova et al, 2002); however, the direct immunomodulatory effects of fermented liquid feed have not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in microflora in response to antibiotics were considered a consequence of a direct effect of antibiotics on the microflora. However, the host itself has a large influence on the composition of the microbiota as a complex and dynamic ecosystem (Reid et al, 2003;Winkler et al, 2007). The different microbial compositions when using antibiotics as antimicrobial growth promoter are a consequence of an altered immune status rather than of a direct effect on the microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…It has been rising number of knowledge how probiotc and prebiotic in feed affect gut and systemic immune competence with changes in gut microbial system (Brisbin et al, 2008;Gionchetti et al, 2006;Janardhana et al, 2009;Kabir, 2009;Lee et al, 2010a and b;Reid et al, 2003;Preidis and Versalovic, 2009;Winkler et al, 2007) although the exact mechanisms that exist in the chicken to control host responses through those non-antibiotics growth promoters are not completely clarified. Probiotics especially lactobacilli could modulate the systemic antibody response to antigens in chicks, and it effect on gut immune response were well studied (Higgins et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to a normal microbial flora early in life allows for a change in the lymphocyte T-helper 1 (Th1)/ lymphocyte T-helper 2 (Th2) balance, favoring a Th1 cell response. 4 Atopic diseases, on the contrary, involve Th2 responses to allergens 5 ; abnormal allergic responses are thought to arise in the absence of a normal gut microbiome while the immune system is still developing, 6,7 producing a shift of the Th1/Th2 cytokine balance toward a Th2 response, and a consequent activation of Th2 cytokines such as interleukin (IL)-4, IL-5, and IL-13, as well as increased production of immunoglobulin (Ig) E. 8 Probiotics, defined as "live microorganisms, which, when administered in adequate amounts, confer a health benefit to the host" by the World Health Organization, 9 can potentially modulate the immune response, resulting in stimulation of Th1 cytokines that can suppress Th2 responses. 8 Several studies were therefore designed to examine the efficacy of probiotics in many allergic disorders.…”
mentioning
confidence: 99%